Entre as fronteiras e os limites do cárcere: geografias do regime semiaberto de privação de liberdade na área metropolitana da Grande Vitória - Bayerl, Moniqui Vassoler (2023)
To understand the dynamics of prison spaces and the different forms of deprivation of liberty, it is important to understand that, according to the Brazilian penal code (BRASIL, 1984), the penalty of deprivation of liberty can be divided into: a fine; penalty restricting rights; and the best known, custodial sentence (imprisonment). The custodial sentence can initially be served in closed, semi-open and open regimes. Being the semi-open regime, which is precisely the criminal modality and the objective of investigation of this research, in it the inmate acquires the opportunity to leave prison spaces to work, study or benefit from temporary exits, but with the condition of good conduct and return to incarceration, that is, in semi-open prison the prisoner has the opportunity to access spaces of freedom while still in the prison system. And amid bibliographical research, it became notable that the works produced on subjects and prison spaces in Geography are, for the most part, limited to the closed regime of deprivation of liberty. Therefore, it becomes a challenge to go beyond the closed regime, aiming to geographically analyze the spatialities, borders, experiences and experiences of internal subjects in the semi-open regime of deprivation of liberty. And according to the Dictionary of the Portuguese Language (DICIO, 2020), the word semi means “being in the middle”, that is, it is about what has not yet been concluded. Would the semi-open regime then be a path to freedom? Would it be a border between prison and freedom spaces? The aim, then, as a central objective of the research and contribution to the disciplinary field of prison studies, is to geographically analyze the spatialities and experiences of subjects who live on the border between prison and freedom spaces in the metropolitan region of Vitória in the state of Holy Spirit. To achieve this, dialogue with different concepts becomes essential, such as theoretical discussion regarding prison spaces and their power relations and about territories, borders and limits. Discussions and debates that are central to the research, and which are methodologically linked to qualitative research and fieldwork with the application of analytical instruments with the subjects and prison spaces of interest, also combined with the experiences lived by the author herself, form the pillars of this search. The work therefore has as its field and target audience the Espírito Santo prison system and inmates of the semi-open regime. Where the research considers the daily experiences, experiences and narratives of those who feel them, live them and construct them in their own, joint and singular way in the semi-open regime of deprivation of liberty.